2017
DOI: 10.3389/fmicb.2017.02147
|View full text |Cite
|
Sign up to set email alerts
|

Camelina Seed Supplementation at Two Dietary Fat Levels Change Ruminal Bacterial Community Composition in a Dual-Flow Continuous Culture System

Abstract: This experiment aimed to determine the effects of camelina seed (CS) supplementation at different dietary fat levels on ruminal bacterial community composition and how it relates to changes in ruminal fermentation in a dual-flow continuous culture system. Diets were randomly assigned to 8 fermenters (1,200–1,250 mL) in a 2 × 2 factorial arrangement of treatments in a replicated 4 × 4 Latin square with four 10-day experimental periods that consisted of 7 days for diet adaptation and 3 days for sample collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 62 publications
7
20
0
Order By: Relevance
“…Total genomic DNA was extracted separately from solid and liquid samples following the methods of Stevenson and Weimer (2007) and described by Dai et al (2017). This method is similar to the phenol-chloroform with bead beating II method (Henderson et al, 2013), which is likely to yield DNA representative of the BCC.…”
Section: Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total genomic DNA was extracted separately from solid and liquid samples following the methods of Stevenson and Weimer (2007) and described by Dai et al (2017). This method is similar to the phenol-chloroform with bead beating II method (Henderson et al, 2013), which is likely to yield DNA representative of the BCC.…”
Section: Dna Extractionmentioning
confidence: 99%
“…Sequence processing and data analysis were performed using mothur v.1.38.1 following the MiSeq SOP (Kozich et al, 2013) and described in detail by Dai et al (2017). Briefly, the unique sequences were aligned against the SILVA 16S rRNA gene reference alignment database (v128, Pruesse et al, 2007) and operational taxonomic units (OTU) classified based on the Green-Genes database (Desantis et al, 2006), August 2013 release, with a bootstrap cutoff of 80.…”
Section: Bacterial Sequence Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These results, combined with the reduction in NDF digestibility and acetate concentration, strengthen the hypothesis that SCAM depressed cellulolytic bacteria population. In fact, in a study evaluating the effects of feeding camelina seed in the ruminal bacterial community composition, Dai et al (2017) reported that camelina diets suppressed cellulolytic bacteria. One possible explanation for that might be the fact that camelina has 73.9% of total fatty acids in the form of PUFA (Hurtaud and Peyraud, 2007), which are associated with possible detrimental effects on cellulolytic bacteria (Maczulak et al, 1981;Maia et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fat shapes rumen microbiota, most of the study focused on the adult ruminant [10], little is known about the effect of pre-weaning diet on the establishment of the rumen microbiota. Although most of the milk replacer directly went into abomasums due to the closure of the esophageal groove by reflex action, part of the milk leaked into the rumen [11], which becomes substrate with starter for ruminal microbes.…”
Section: Introductionmentioning
confidence: 99%